Development of Academic Skills at the Educational Systems: - Muxtorqizi, Ganixodjayeva Arofat (European Journal of Life Safety and Stability (2660-9630), 2021)
To be successful in academic life, students must develop skills and knowledge that will enable them to acquire the necessary skills to survive in the academic environment, continue their education throughout their lives, and prepare for professional life. The ability to learn effectively is one of the essential skills that should be developed during their studies so that they develop a good learning habit that they can use even after graduation.